ANALYSIS OF FACTORS CAUSING INCOME INEQUALITY IN EAST JAVA PROVINCE - Alya Haidarini Sahira (Jurnal Paradigma Multidisipliner (JPM), 2022)
Income inequality is a major problem that commonly occurs in developing countries. Income inequality is usually characterized by a gap between low-income and high-income people. This research was conducted with the aim of knowing the effect of total population, GDP per capita, and open unemployment rates on income inequality in East Java Province from 1990-2020. The data processed in this study uses secondary data obtained from the Central Bureau of Statistics and previous research. The data obtained were analyzed using ECM analysis which was processed using the Eviews10 program. In the short term, the variable population size, GDP per capita, and the open unemployment rate have no effect on income inequality. Meanwhile, in the long run only the population variable has an effect on income inequality. Keywords: Income Inequality; GRDP at capita; Income Distribution; East Java; ECM analysis